Religious Authority and Family Law Reform in Indonesia: The Response and Influence of the Indonesian Ulema Council on Interfaith Marriage - Mustofa, Kholifatun Nur; Fakhria, Sheila; Quintana, Milla Khumayla; Tauziri, Yusup; Nainin, Dasrizal Marah (JURIS (Jurnal Ilmiah Syariah), 2024)
This paper examines the response and attitude of the Indonesian Ulema Council (MUI) to practice interfaith marriage and study the influence of MUI in the development of the rules of interfaith marriage. Research data is taken through online media accessible in the news online, website and fatwa MUI as well as other supporting sources. This paper argues that MUI keep trying to assert the prohibition of marriage between religions through their fatwas and through responses in the media to the proliferation of interfaith marriages. Other responses are also in presented by the Indonesian Ulema Council through information when asked for opinions in the Judicial Review and when asked for the same opinion on social media. MUI's attitude is also shown through the lawsuit against the Surabaya District Court for granting interfaith marriage. This paper found that the effect of MUI on marriage rules was different from religion can be seen clearly by issuing rules regarding interfaith marriage, through Circular Letter Number 2 of 2023 concerning the prohibition of judges from granting a marriage of different faiths so that the Indonesian Ulema Council seems to provide the influence on law is particularly high in interfaith marriages in Indonesia.